Three-Dimensional Graphene-Decorated Copper-Phosphide (Cu3P@3DG) Heterostructure as an Effective Electrode for a Supercapacitor - Kumar, Subodh; Aziz, S. K. Tarik; Kumar, Sushil; Riyajuddin, Sk; Yaniv, Gili; Meshi, Louisa; Nessim, Gilbert D.; Ghosh, Kaushik (Frontiers in Materials, 2020)
Transition metal phosphides are already a well-practiced domain of interest due to their energy storage capacitance, superior metalloid characteristics and decent electrical conductivity. In order to achieve commercially viable outcome, these electrodes are subjected to fabricate with interconnected carbonaceous materials. Herein, we report a facile strategy to synthesize hexagonal copper phosphide (Cu3P) platelets using an atmospheric chemical vapor deposition (CVD) system along with proper alteration of ingredients 3-dimensional graphene (3DG) as Cu3P@3DG nanohybrid with operative coulombic efficient supercapacitor. The nano-hybrid Cu3P@3DG delivers specific capacitance (Csp) of 1095.85 F/g at 10 mV/s with cycling stability of 95% capacitive retention after 3000 cycles at 8.97 A/g. The Csp is almost 5.6 times higher and stability is 1.2 times higher compared to the bare Cu3P platelet. The asymmetric supercapacitor also has been made-up using Cu3P@3DG, and activated carbon (AC) as the cathode and anode (Cu3P@3DG//AC) respectively, revealed a high specific capacity (108.78 F/g), energy density (8.23 Wh/kg) and power density (439.6 W/kg). Moreover, this asymmetric supercapacitor showed an excellent life cycle, 5500 consecutive charge/discharge cycles with 96 % coulombic efficiency. As best of our knowledge, our proposed all-solid-state hybrid will be an ideal choice of forthcoming supercapacitor devices.